Substitusi Tepung Sorgum Terhadap Elongasi Dan Daya Terima Mie Basah Dengan Volume Air Yang Proporsional - Fitriani, Rosmauli Jerimia, Rusdin Rauf, STP, MP, Eni Purwani, S.Si, M.Si (2016)
Introduction: Noodle is a food that much favored by different age groups, which are from children to adults. Generally, wet noodles made from wheat flour. However, considering the nutritional value and efforts to use local food, sorghum flour can be used as raw material for making wet noodle. Sorghum is a plant that can adapt to dry conditions with short lifespan. Sorghum has 3.65 % fat , 2.74 % crude fiber , 10.11 % protein and 80.42 % starch . Different flour require different amounts of water . Making wet noodle from sorghum flour with proportional volume of water can influence the elongation and acceptance of the noodle. Objective: To determine the elongation and acceptance of wet noodles with substitution of sorghum flour using, water volume which is determined proportionally . Methods: The research was experimental method with a completely randomized design using 4 treatments ( 0 % , 10 % , 20 % and 30 % ). The statistical analysis of elongation and acceptance value using one way ANOVA test with significance level of 95% and continued by Duncan Multiple Range Test ( DMRT ) Results: Water absorption of wheat flour which was substituted with sorghum flour ranged between 179.83 % -180.53 % , proportional volume of water to make wet noodle dough which was substituted with sorghum flour was 17.5 ml / 100gram materials , the highest elongation wet noodle was with the substitution of 0 % , and the lowest was with 30 % substitution. Most of panelists prefer the wet noodles which was substituted with sorghum flour 0 % and followed by the substitution of 10 % Conclusion: There is an influence of sorghum flour substitution on the wet noodle elongation. There is an influence of sorghum flour substitution on the wet noodle color acceptability . Suggestion: Further studies should be done to increase the acceptance of color in noodles made from mixture of flour and sorghum flour . Pendahuluan : Mie merupakan makanan yang banyak digemari berbagai kalangan dari anak sampai dewasa. Umumnya mie basah terbuat dari tepung terigu, namun dengan mempertimbangkan nilai gizinya dan upaya pemanfaatan pangan lokal maka tepung sorgum dapat dijadikan bahan baku pembuatan mie basah. Sorgum merupakan tanaman yang dapat beradaptasi pada kondisi kering dengan umur tanam yang pendek. Tepung sorgum memiliki 3,65% lemak, 2,74% serat kasar, 10,11% protein, 80,42% pati. Tepung yang berbeda membutuhkan jumlah air yang berbeda. Pembuatan mie basah tepung sorgum dengan volume air yang proporsional akan mempengaruhi elongasi dan daya terima. Tujuan : Mengetahui elongasi dan daya terima mie basah dengan substitusi tepung sorgum dengan menggunakan volume air yang ditentukan secara proporsional. Metode Penelitian : Metode penelitian ini adalah eksperimental dengan rancangan acak lengkap menggunakan 4 perlakuan (0%, 10%, 20% dan 30%). Analisis statistik nilai elongasi dan daya terima menggunakan uji one way anova dengan taraf signifikan 95% dan dilanjutkan dengan uji Duncan Multiple Range Test (DMRT). Hasil : Daya serap air tepung terigu yang disubstitusi tepung sorgum berkisar antara 179,83%-180,53%, volume air proporsional untuk membuat adonan mie basah yang disubstitusi tepung sorgum yaitu 17,5 ml/100gram bahan, elongasi mie basah yang paling tinggi dimiliki oleh substitusi 0%, dan paling rendah dengan substitusi 30 % Sebagian besar panelis lebih menyukai mie basah yang disubstitusi tepung sorgum 0 % dan diikuti oleh substitusi 10% Kesimpulan : Ada pengaruh substitusi tepung sorgum terhadap elongasi mie basah. Ada pengaruh substitusi tepung sorgum terhadap daya terima warna mie basah. Saran : Perlu dilakukan penelitian lebih lanjut untuk meningkatkan daya terima warna pada mie yang dibuat dari campuran tepung terigu dan tepung sorgum.